Christ-Siemens-Touraine Syndrome - A Case Report with Review of literature - D’souza, Valen Dela; Rao, Prasanna Kumar; Kini, Raghavendra (Journal of Oral Diagnosis, 2020)
Ectodermal dysplasia (ED) is a hereditary disorder characterized by developmental defects of structures derived from the ectoderm. The most prevalent form of ED is hypohydrotic ectodermal dysplasia also known as Christ-Siemens-Touraine syndrome. This case report illustrates the manifestations and diagnosis of a twenty-two-year-old male patient with hypohydrotic ectodermal dysplasia with a brief review of literature.